The effects of Origanum onites in streptozotocin-induced diabetes mellitus in rats - POLAT, ELİF BEYZANUR; TAŞKIN, TURGUT; BİTİŞ, LEYLA; ELÇİOĞLU, HATİCE KÜBRA (My University, 2022)
© 2022 Marmara University Press.Diabetes mellitus is a chronic disease characterized by decreased insulin synthesis and/or increased blood glucose due to insulin resistance. In this study, streptozotocin (STZ)-induced diabetic rats were evaluated and it was aimed to investigate the protective effects of Origanum onites L. (OO) against possible changes in these parameters. Male Sprague-Dawley rats weighing 300-400g were divided into three groups control (C), diabetes mellitus (DM) and diabetes mellitus + OO (OO group). DM was induced by administration of STZ 60 mg/kg dose intraperitoneally (i.p.) after 48 hours, rats with blood glucose values higher than 200 mg/dL were considered DM. Origanum extract was administered i.p. to the OO group at 50 mg/kg per day for 6 weeks. Serum AST, ALT, creatinine, and inflammatory cytokine levels were measured. MDA and GSH levels were measured in liver tissues. AST, ALT, creatinine, and MDA levels were found to be increased in the DM group, while a significant decrease in these levels was observed in the treated group. While GSH values fell in the DM group, a significant increase occurred in the OO group (n=6, p<0.0001; two-way ANOVA). When the plasma levels of cytokines were examined, an increase was observed in the DM group and a significant decrease was observed in the OO group. When we evaluate our findings, we think that OO has a protective effect against complications that may occur in DM by preventing oxidant damage and inflammation. Further studies are needed on the protective effects of OO in DM.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Diabetes mellitus; inflammatory cytokine; liver; Origanum onites; oxidative stress; Diabetes mellitus; oxidative stress; liver; Origanum onites; inflammatory cytokine